2022
DOI: 10.1097/corr.0000000000002164
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Inconsistency and Variability Exists Among Minimum Clinically Important Differences for Shoulder Arthroplasty Outcomes: A Systematic Review

Abstract: Background As the value of patient-reported outcomes becomes increasingly recognized, minimum clinically important difference (MCID) thresholds have seen greater use in shoulder arthroplasty. However, MCIDs are unique to certain populations, and variation in the modes of calculation in this field may be of concern. With the growing utilization of MCIDs within the field and value-based care models, a detailed appraisal of the appropriateness of MCID use in the literature is necessary and has not been systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The MCID values have been shown to be highly variable between previous publications. 12 It is likely that Patient Acceptable Symptomatic State values are variable as well; however, further study is warranted to make this conclusion. This study included those who “met” surgical expectations for pain relief in the substantially improved group with the assumption that patients’ surgical expectations are likely a significant improvement in their preoperative pain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The MCID values have been shown to be highly variable between previous publications. 12 It is likely that Patient Acceptable Symptomatic State values are variable as well; however, further study is warranted to make this conclusion. This study included those who “met” surgical expectations for pain relief in the substantially improved group with the assumption that patients’ surgical expectations are likely a significant improvement in their preoperative pain.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a systematic review by Kolin et al found similar heterogeneity previously reported MCID values for shoulder arthroplasty outcome measurements. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The MCID values may vary according to disease, interventions, and baseline characteristics, including socio-demographic and clinical characteristics; therefore, MCID may vary by gender, education level, type of CHD, and different comorbidities in this study ( 47 , 70 ). In particular, studies found that the prognosis of male patients with CHD after PCI was better than that of female patients; the mortality, incidence of major adverse cardiovascular events, and bleeding events after PCI in female patients were higher than those in male patients; and the health status (such as HRQoL, mental health) of female patients after PCI was worse than that of male patients ( 71–73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this month’s Clinical Orthopaedics and Related Research ® , Kolin et al [4] systematically reviewed 43 studies on the use of the MCID to assess the outcomes of total shoulder arthroplasty. They aimed to closely evaluate how MCIDs were used and reported, and to determine whether there was any meaningful consistency.…”
Section: Where Are We Now?mentioning
confidence: 99%